Pengaruh Shopping Lifestyle Terhadap Impulse Buying Mahasiswa/I Politeknik Negeri Bandung Pada Marketplace Shopee - Khaerany Aulia (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study is to test and empirically prove the influence of an impulsive shopping lifestyle on students at the Bandung State Polytechnic, especially at Shopee. The object of this study was students of the Bandung State Polytechnic with a sample of 105 respondents. The methods used consist of validity tests, reliability tests, descriptive analysis, regression analysis, and correlation test analysis. Data collection is done by filling out a questionnaire on a google form. Shopping lifestyle has an influence of 19.8% on impulse purchases of Bandung State Polytechnic students. Meanwhile, the other 80.2% were influenced by other variables outside the study.he purpose of this study